Adoption of Agroforestry-Porang Model for Land Utilization under Teak Stands - Hermudananto Hermudananto; Dwiko Budi Permadi; Ratih Madya Septiana; Slamet Riyanto; Andita Aulia Pratama (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Banyusoco village in Gunungkidul has more than 60% of its land as state forests managed by several forest farmer groups in Hutan Kemasyarakatan scheme (HKm) majority planted Teak (Tectona grandis). Problem of "delayed" revenue through harvesting slow-growing Teak stands could be resolved by planting a type of tubers or empon-empon under the stand, so that forest floor may earn additional income. Our community service focuses on introduction of Porang tuber plants (Amorphophallus oncocphyllus) to a) increase environmental knowledge and skills of farmers in agroforestry-Porang cultivation; b) increase knowledge and skills of farmers in harvesting and managing post-harvest of Porang; c) increase farmers' income from Porang. Our first of three year activities program included institutional workshops and introduction of Porang cultivation, procurement of Porang seeds, development of demonstration plot, and facilitation on planting Porang under stands. Temporary result was a 0.5 ha-demonstration plot with 4,000 seeds supporting by HKm "Sedyo Makmur" which positively impacts in a) fostering cohesiveness of members with mutual cooperation every Thursday (Kamisan) in preparing and maintaining land; b) increasing members' understanding in cultivation Porang; c) becoming a portfolio in national HKm competition. Following year's community empowerment program continues to be focused on maintaining, harvesting and marketing Porang.